TRADISI TIMBA LAOR & KETAHANAN SOSIAL MASYARAKAT WAELUA - Soulisa, Walid; Tihurua, Ode Zulkarnain Sahji (JURNAL MEDIASI, 2022)
This study looks at the tradition of timba laor in the Waelua community as a creation of social resilience in the east monsoon. The research was conducted using qualitative research and data collection techniques in the form of in-depth interviews, involved observations, and documentation. In analyzing research findings, we use the theory of social resilience from Keck & Sakdaporlak (2020). We elaborate on this social resilience theory with the concept of a socio-ecological system used by Howard (2010). This study found that the timba laor tradition as social resilience is knowledge that comes from the experience of the Waelua people in dealing with the nature in which they live. Social resilience is not only born from the thoughts of humans but also based on the stimulus from the nature in which they live. Culture-based social resilience is a model of social resilience that must be preserved and developed. Currently, mankind on this earth is in an era of a very worrying natural crisis or an era called the "Anthropocene". The natural crisis as a result of human actions that are greedy to take advantage of nature must be stopped and we must return to cultural diversity which is used as social resilience.